Indirect determination of serum creatinine reference intervals in a Pakistani pediatric population using big data analytics - Ahmed, Sibtain; Zierk, Jakob; Siddiqui, Imran; Khan, Aysha Habib (World Journal of Clinical Pediatrics, 2021)
BACKGROUND The indirect methods of reference intervals (RI) establishment based on data mining are utilized to overcome the ethical, practical challenges and the cost associated with the conventional direct approach. AIM To generate RIs for serum creatinine in children and adolescents using an indirect statistical tool. METHODS Data mining of the laboratory information system was performed for serum creatinine analyzed from birth to 17 years for both genders. The timeline was set at six years from January 2013 to December 2018. Microsoft Excel 2010 and an indirect algorithm developed by the German Society of Clinical Chemistry and Laboratory Medicine’s Working Group on Guide Limits were used for the data analysis. RESULTS Data were extracted from 96104 samples and after excluding multiple samples for the same individual, we calculated RIs for 21920 males and 14846 females, with stratification into six discrete age groups. CONCLUSION Serum creatinine dynamics varied significantly across gender and age groups.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Creatinine; Data mining; Indirect; Pakistan; Pediatric; Reference intervals